Health management of beef cattle: A case study - Hartady, Tyagita; Widyastuti, Rini; Hiroyuki, Andi (Faculty of Animal Science, Universitas Brawijaya, 2021)
The reports about how are farmers able to prevent, identify and treat the animal diseases to not get worse while the production is still maintained, are limited. The application of the standard good farming practices is also not well documented. Therefore, to provide adequate information about beef cattle health management in smallholders, especially in Indonesia; this study was conducted at